THE ROLE OF NAHDLATUL ULAMA IN PROMOTING GOVERNMENT TRANSPARENCY AND ACCOUNTABILITY IN NORTH SUMATRA: AN ISLAMIC POLITICAL THOUGHT PERSPECTIVE - Wahyu Septiawan; Katimin (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the role of Nahdlatul Ulama in promoting government transparency and accountability in North Sumatra from the perspective of Islamic political thought. The study underscores the importance of implementing the principles of good governance to foster a system of governance that is transparent, accountable, and responsive to public needs. As one of Indonesia’s largest Islamic civil society organizations, Nahdlatul Ulama plays a strategic role in exercising social oversight, advocating public policy, and providing political education grounded in Islamic ethical values. This research employed a qualitative descriptive-analytical approach based on library research and document analysis related to Islamic political thought and the socio-political practices of Islamic organizations at the regional level. The analysis was guided by the Islamic political concepts of amānah (trustworthiness), justice (ʿadl), consultation (shūrā), and ḥisbah as the principal analytical framework. The findings reveal that Nahdlatul Ulama contributes significantly to strengthening transparency and accountability in governance through policy advocacy, the promotion of public participation, and moral oversight of state administrators. These findings demonstrate that Islamic political thought provides a robust normative foundation for civil society participation in monitoring public authority and fostering governance that is oriented toward the public interest.